Association analysis and functional follow-up identified common variants of JAG1 accounting for risk to biliary atresia - Bai, Mei-Rong; Pei, Hao-Yue; Zhou, Ying; Song, Huan-Lei; Pan, Wei-Hua; Gong, Yi-Ming; Wu, Wen-Jie; Yu, Wen-Wen; Cui, Meng-Meng; Gu, Bei-Lin; Chu, Xun; Cai, Wei (Frontiers in Genetics, 2023)
Background: Biliary atresia (BA) is a destructive, obliterative cholangiopathy characterized by progressive fibro-inflammatory disorder and obliteration of intra- and extrahepatic bile ducts. The Jagged1 (JAG1) gene mutations have been found in some isolated BA cases. We aim to explore the association of common variants in JAG1 with isolated BA risk in the Chinese Han population. Methods: We genotyped 31 tag single nucleotide polymorphisms covering the JAG1 gene region in 333 BA patients and 1,665 healthy controls from the Chinese population, and performed case-control association analysis. The expression patterns of JAG1 homologs were investigated in zebrafish embryos, and the roles of jag1a and jag1b in biliary development were examined by morpholino knockdown in zebrafish. Results: Single nucleotide polymorphisms rs6077861 [PAllelic = 1.74 × 10−4, odds ratio = 1.78, 95% confidence interval: 1.31–2.40] and rs3748478 (PAllelic = 5.77 × 10−4, odds ratio = 1.39, 95% confidence interval: 1.15–1.67) located in the intron region of JAG1 showed significant associations with BA susceptibility. The JAG1 homologs, jag1a and jag1b genes were expressed in the developing hepatobiliary duct of zebrafish, especially at 72 and 96 h postfertilization. Knockdown of both jag1a and jag1b led to poor biliary secretion, sparse intrahepatic bile duct network and smaller or no gallbladders compared with control embryos in the zebrafish model. Conclusion: Common genetic variants of JAG1 were associated with BA susceptibility. Knockdown of JAG1 homologs led to defective intrahepatic and extrahepatic bile ducts in zebrafish. These results suggest that JAG1 might be implicated in the etiology of BA.